BEHIND THE BELT : The consequences of the Belt and Road – Initiative in Sri Lanka and Djibouti - Mutanen, Lari (My University, 2023)
The Belt and Road – Initiative (BRI) is a series of Chinese-funded large-scale infrastructure projects across the globe that was started in 2013. The BRI is connected to the developing world to increase global connectivity and facilitate economic growth in developing countries. The BRI is an influential initiative, but the influence is not necessarily positive. The research question of this thesis examines the political, economic and geopolitical consequences of the BRI in two developing countries, Sri Lanka and Djibouti. The outlook of this thesis is conceptual. The methodology of the thesis is based on a qualitative research approach with primary and secondary data. The primary data consists of two semi-structured themed interviews with experts of contemporary China and International Business. The secondary data is a sample of peer-reviewed research papers from a vast body of literature examined with document analysis. The interviews were interpreted with a mixture of validation and philosophical hermeneutics. The research question was answered in the following manner. The effect of the BRI is strong and has its political, economic and geopolitical dimensions. In the political sphere, the interest of Chinese policymakers means that developing countries in the BRI face consequences ranging from the shrinking of local political space to overt interference in the country’s internal matters. This happens because the BRI is important for the survival of China’s political elite. On the economic side, the BRI represents a radical transformation that the developing member-states are not always ready for. This is due to the underdeveloped nature of local institutions that are unable to prevent the BRI funds from strengthening the dysfunctional nature of the local political sphere. Given that China’s role as a lender in the developing world only seems to increase, the disruptive effects of the BRI can leave individual members in a difficult place. Geopolitically, the BRI consequences mirror China’s rising global stature. The impact of these consequences is varied depending on the issues as China’s geopolitics exist in a continuum between realism and liberalism. The BRI can be viewed as a form of developmental assistance, but is also very relevant to China’s aggressive defense of its interests with “Wolf-Warrior Diplomacy”. The BRI also reflects China’s rising position as the slogans of Xi Jinping gradually become a reality in the developing world. However, this thesis argues that China’s recent history is still relevant and partly explains the misallocation of capital in the developing world. At the end of the day, the BRI appears to be a path of least resistance for China; the country is present in countries where it feels at home. The BRI merely facilitates such convenience.

Uusi Silkkitie on sarja kiinalaisrahoitteisia infrastruktuurihankkeita, jotka aloitettiin vuonna 2013 tavoitteena lisätä kehittyvien talouksien globaalia linkittyneisyyttä. Silkkitiehankkeella on suuri vaikutus kehittyviin maihin eikä tämä vaikutus ole aina positiivista. Tämä tutkielma tarkastelee Silkkitiehankkeen vaikutuksia kehittyvissä maissa käsiteanalyyttisesti ja sen tavoitteena on löytää selityksiä hankkeen laajoille paikallisille vaikutuksille. Sri Lankaa ja Djiboutia käytetään tässä tutkielmassa esimerkkeinä silkkitiehankkeen suurista paikallisista vaikutuksista. Tutkimuskysymys tarkastelee Uuden Silkkitiehankkeen poliittisia, taloudellisia ja geopoliittisia vaikutuksia Sri Lankan ja Djiboutin kaltaisissa kehittyvissä maissa. Tutkielma on laadullinen. Tämän tutkielman aineisto perustuu primääri- ja sekundääridataan. Tutkielman primääridata käsittää kahden Kiinan ja Kansainvälisen Liiketoiminnan asiantuntijan puolistrukturoidut teemahaastattelut ja sekundääridata on otos Uudesta Silkkitiestä julkaistuja vertaisarvioituja tutkimuksia. Haastattelut tutkittiin validaatiohermeneutiikan ja filosofisen hermeneutiikan yhdistelmällä. Tutkimuskysymykseen vastattiin seuraavanlaisesti. Uuden Silkkitien vaikutus kehittyvissä maissa on voimakas ja tämä vaikutus näkyy poliittisesti, taloudellisesti ja geopoliittisesti. Poliittisessa sfäärissä kiinalaisen eliitin intressit tarkoittavat sitä, että paikallisella tasolla maan poliittinen liikkumavara vähintäänkin kaventuu. Pahimmassa tapauksessa ulkovaltojen poliittinen vaikuttaminen on täysin avointa. Kiinan poliittisen eliitin selviytymissuunnitelmat tarkoittavat sitä, että Kiinan intressit dominoivat jäsenmaiden paikallisella poliittisella tasolla. Taloudellisesti tarkasteltuna, Uusi Silkkitie johtaa paikallistalouksien radikaaliin transformaatioon hankkeen valtavasta koosta johtuen. Kehittyvien maiden heikot ja puutteelliset instituutiot eivät pysty estämään silkkitiehankkeen rahavirtojen kanavoitumista poliittisen vallankäytön välineeksi. Tämä tarkoittaa paikallisen politiikan toimimattomien piirteitten vahvistumista. Koska Kiina on erittäin tärkeä lainoittaja kehittyville talouksille, silkkitiehankkeen disruptiivinen vaikutus voi tehdä yksittäisten maitten asemasta vaikean. Geopoliittisesti tarkasteltuna silkkitiehankkeen vaikutus toimii peilinä Kiinan nousevalle globaalille asemalle. Tämä vaikutus riippuu siitä, kuuluuko kyseinen asia Kiinan geopoliittisen jatkumon liberaaliin vai realistiseen päähän. Uusi Silkkitie on kyllä kehitysapua, mutta myös Kiinan ydinintressien armotonta puolustamista ”susisoturidiplomatian” voimin. Merkillepantavaa on se, että Xi Jinpingin sloganit muuttuvat ennen pitkää todellisuudeksi kehittyvien jäsenmaitten paikallisella tasolla. Kiinan lähihistorian käänteet kuitenkin kummittelevat taustalla ja vaikuttavat investointien kohdentumiseen. Loppujen lopuksi Kiina menee siitä mistä aita on matalin koska se haluaa saada eniten aikaan pienimmällä vaivannäöllä. Kiina on investoinut maihin, joissa se kokee olevansa kuin kotonaan. Uusi Silkkitie vain helpottaa tätä prosessia.
Keywords: BRI, China, Developing countries, Politics, Geopolitics, Economic consequences, Sri Lanka, Djibouti